PENERAPAN TEKNIK LUCK OF THE DRAW UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARANPAI SISWA KELAS IV DI SD NEGERI 003 PULAU KOPUNG SENTAJO KECAMATAN SENTAJO RAYA - Nurdiana Nurdiana; Sopiatun Nahwiyah; Helbi Akbar (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2020)
The purpose of this study was to determine the increase in learning outcomes and the factors that influence learning outcomes in the field of study of PAI fourth grade students by applying the Luck of the Draw technique in SD Negeri 003 Kopung Sentajo Island, Sentajo Raya District. The subjects in this study were one PAI teacher and all fourth grade students of SD Negeri 003 Kopung Sentajo Island, Sentajo Raya District, totaling 20 people consisting of 8 male students and 12 female students, while as an object was the application of the Luck technique of the Draw can improve student learning outcomes in grade IV in the field of PAI study at SD Negeri 003 Kopung Sentajo Island. Based on the results of data collection by means of observation, tests, interviews and documentation, then analyzed the data using graphs it can be concluded that: The application of Luck of the Draw technique can improve learning outcomes of fourth grade students in Islamic Religious Education in State Elementary School 003 Kopung Sentajo Island District Sentajo Raya, this is evidenced by an increase in student learning outcomes ranging from pre Cycle to Cycle III with a percentage of 74.55 (pre Cycle), 76.55 (Cycle I), 79.50 (Cycle II) and 85.40 (Cycle III). So student learning outcomes IV at SD Negeri 003 Kopung Sentajo Island continues to increase according to the evaluation results.